2008
DOI: 10.1128/jvi.00826-08
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hepatitis C Virus Nonstructural Protein 5A with Core Protein Is Critical for the Production of Infectious Virus Particles

Abstract: Nonstructural protein 5A (NS5A) of the hepatitis C virus (HCV) possesses multiple and diverse functions in RNA replication, interferon resistance, and viral pathogenesis. Recent studies suggest that NS5A is involved in the assembly and maturation of infectious viral particles; however, precisely how NS5A participates in virus production has not been fully elucidated. In the present study, we demonstrate that NS5A is a prerequisite for HCV particle production as a result of its interaction with the viral capsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
391
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(419 citation statements)
references
References 59 publications
23
391
1
4
Order By: Relevance
“…3(d), the precise mechanism of action of the single-domain intrabodies that causes decreases in propagation of HCV remains unclear. It is possible that these intrabodies affect processes important for early steps in virion assembly, such as core-RNA binding, dimerization of core, localization of core with lipid droplets or the interaction between core and NS5A (Counihan et al, 2011;Masaki et al, 2008). Furthermore, as anti-core intrabodies interfere with NFk B signalling induced by HCV core, these intrabodies can be applied to dissect the mechanisms underlying the ability of core to regulate cellular gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…3(d), the precise mechanism of action of the single-domain intrabodies that causes decreases in propagation of HCV remains unclear. It is possible that these intrabodies affect processes important for early steps in virion assembly, such as core-RNA binding, dimerization of core, localization of core with lipid droplets or the interaction between core and NS5A (Counihan et al, 2011;Masaki et al, 2008). Furthermore, as anti-core intrabodies interfere with NFk B signalling induced by HCV core, these intrabodies can be applied to dissect the mechanisms underlying the ability of core to regulate cellular gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…The NS5A protein of CSFV, BVDV and HCV has been shown to be an essential replicase component (Masaki et al, 2008;Tellinghuisen et al, 2006;Sheng et al, 2010), thus, ANXA2 might participate in the CSFV production process by binding to NS5A protein. In fact, ANXA2 has been found to be involved in the formation of HCV replication complex on the lipid raft (Saxena et al, 2012).…”
Section: W I T H O U T S I R N a C O N T R O L S I R N A A N T I -A Nmentioning
confidence: 99%
“…Previous reports showed that HCV NS5A is necessary for HCV assembly and production and interacts with ANXA2 (Appel et al, 2008;Masaki et al, 2008;Saxena et al, 2012). To investigate whether ANXA2 interacts with CSFV NS5A, several NS5A mutants (Fig.…”
mentioning
confidence: 99%
“…HCV NS5a is a phosphoprotein involved in replication and virus-particle formation. In both processes, the phosphorylation status of NS5a has been shown to be critical (Appel et al, 2005;Evans et al, 2004;Masaki et al, 2008;Tellinghuisen et al, 2008). The multifunctional protein NS3 might be regulated in a similar way.…”
mentioning
confidence: 99%